2014
DOI: 10.1038/onc.2014.158
|View full text |Cite|
|
Sign up to set email alerts
|

IL-6 secreted by cancer-associated fibroblasts induces tamoxifen resistance in luminal breast cancer

Abstract: Cancer-associated fibroblasts (CAFs) have been implicated in the development of resistance to anticancer drugs; however, the role and mechanism underlying CAFs in luminal breast cancer (BrCA) tamoxifen resistance are unclear. We found that stromal fibroblasts isolated from the central or peripheral area of BrCA have similar CAF phenotype and activity. In vitro and in vivo experiments showed that CAFs derived from clinical-luminal BrCAs induce tamoxifen resistance through decreasing estrogen receptor-α (ER-α) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…It is also reported that mCAFs induce high mobility group box 1 and contribute to resistance to doxorubicin in breast cancer cells [120]. A previous study indicated co-culture with breast cancerderived fibroblasts decreased tamoxifen sensitivity in cancer cells and protected them from tamoxifen-induced death; the fibroblastinduced tamoxifen resistance was ascribed to soluble stromal factors such as IL6, MMPs and ECM components including fibronectin [122,124,125]. Notably, significant association was observed between CAF presence and endocrine resistance in several clinical series, as previously mentioned (Table 1).…”
Section: Mcafs Cause Therapeutic Resistancementioning
confidence: 95%
See 1 more Smart Citation
“…It is also reported that mCAFs induce high mobility group box 1 and contribute to resistance to doxorubicin in breast cancer cells [120]. A previous study indicated co-culture with breast cancerderived fibroblasts decreased tamoxifen sensitivity in cancer cells and protected them from tamoxifen-induced death; the fibroblastinduced tamoxifen resistance was ascribed to soluble stromal factors such as IL6, MMPs and ECM components including fibronectin [122,124,125]. Notably, significant association was observed between CAF presence and endocrine resistance in several clinical series, as previously mentioned (Table 1).…”
Section: Mcafs Cause Therapeutic Resistancementioning
confidence: 95%
“…Therefore, much effort has been focused on this area. Interestingly, increasing evidence revealed that mCAFs are a cause of endocrine/chemotherapy and target therapeutic resistance in breast cancer treatment [120][121][122]. Collagen type I secreted by CAFs was demonstrated to decrease chemotherapeutic drug uptake in tumors, and thus plays a significant role in regulating tumor sensitivity to a variety of chemotherapies.…”
Section: Mcafs Cause Therapeutic Resistancementioning
confidence: 99%
“…Upregulation in IL-6 was also observed. IL-6 is reported to impart drug resistance and cancer progression by Janus kinase/signal transducers and activators of transcription (JAK/STAT3) and phosphatidylinositol 3-kinase (PI3K)/AKT pathways in tumor cells [65]. ITAC levels were highly upregulated in treatments when compared to control.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For a long time, it has been suspected that elevated estrogen levels are associated with an increased risk in breast cancer. A recent study Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/25/15 10:38 AM on breast cancer showed that CAF conferred tamoxifen resistance through interleukin-6 (IL-6) [47]. Similarly, in prostate cancer, CAF exerts a mandatory role in prostate cancer progression and favors metastatic dissemination of aggressive lesions [48].…”
Section: Cellular Component Of Connective Tissuementioning
confidence: 98%